CONTRIBUTION OF KNOWLEDGE AND RELIGIOSITY TO INCREASE THE NUMBER OF CUSTOMERS AT ISLAMIC BANK - Dwi Wahyuni, Dayang; Sentika, Dina; Salsabila, Aura (Asian Journal of Islamic Economic Studies, 2024)
This research was motivated by the use of conventional banks, which are more dominant than Islamic banks in Tapan. The purpose of this study is to determine the influence of the level of knowledge and religiosity on customer interest in choosing savings products at Bank Nagari Sharia Unit Tapan Branch. This research uses a quantitative research design. The population in this study is all people who use the Bank Nagari Sharia Unit Tapan Branch. Samples were taken using the Hair formula with a total sample of 55 people. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 21. The results showed that partially and simultaneously, the variables of Knowledge and Religiosity had a significant and positive effect on interest in saving. This result can provide an overview to the bank to pay attention to the level of knowledge and religiosity of customers so that the number of customers increases. Some of them are by providing understanding to the public related to aspects of Sharia that must be considered.